Progress in the application of body fluid and tissue level mRNAs-non-coding RNAs for the early diagnosis and prognostic evaluation of systemic lupus erythematosus - Liang, Jiabin; Xie, Fangmei; Feng, Jie; Huang, Chen; Shen, Jian; Han, Zeping; Luo, Wenfeng; He, Jinhua; Chen, Hanwei (Frontiers in Immunology, 2022)
The diagnosis and differential classification of systemic lupus erythematosus (SLE) is still difficult, especially in patients with early onset of SLE, which is susceptible to systemic multi-organ damage, difficulties in individualized treatment, and even serious complications. At present, the diagnosis is mainly based on clinical manifestations and detection of serological antinuclear antibodies. The pathogenesis of SLE involves multiple factors, is clinically heterogeneous, and lacks specific biomarkers. Therefore, it is necessary to explore some new biomarkers for the diagnosis and subtype classification of SLE. Non-coding RNA molecules are composed of microrNA, long non-coding RNA, small nucleolar RNA and circular RNA. They play an important role in the occurrence and development of diseases and are widely used in the early diagnosis and prognosis of autoimmune diseases. In this review, we focus on the research progress in the diagnosis and prognosis assessment of SLE from the humoral to tissue level (mRNA-ncRNA).